2017
DOI: 10.1111/mpp.12525
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of silencing suppressor p24 of Grapevine leafroll‐associated virus 2

Abstract: Grapevine leafroll-associated virus 2 (GLRaV-2) p24 has been reported to be an RNA silencing suppressor (RSS). However, the mechanisms underlying p24's suppression of RNA silencing are unknown. Using Agrobacterium infiltration-mediated RNA silencing assays, we showed that GLRaV-2 p24 is a strong RSS triggered by positive-sense green fluorescent protein (GFP) RNA, and that silencing suppression by p24 effectively blocks the accumulation of small interfering RNAs. Deletion analyses showed that the region of amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Leaves of GFP-expressing transgenic N. benthamiana line 16c [ 37 ] were infiltrated with cultures harboring pGD–GFP and pGD–p24 G1 . Coinfiltration of pGD–GFP with an empty vector (pGD), or with pGD–p19 [ 27 ] expressing p19 of TBSV, a well-characterized suppressor, was used as negative and positive controls, respectively. Leaf patches expressing p24 G1 showed strong GFP fluorescence three days post-infiltration (dpi), similar to that with expression of p19 ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Leaves of GFP-expressing transgenic N. benthamiana line 16c [ 37 ] were infiltrated with cultures harboring pGD–GFP and pGD–p24 G1 . Coinfiltration of pGD–GFP with an empty vector (pGD), or with pGD–p19 [ 27 ] expressing p19 of TBSV, a well-characterized suppressor, was used as negative and positive controls, respectively. Leaf patches expressing p24 G1 showed strong GFP fluorescence three days post-infiltration (dpi), similar to that with expression of p19 ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…Basic aa residues are critical for protein nuclear transport [ 40 ], as well as for viral RSS binding of siRNA and suppression of RNA silencing [ 10 , 12 , 27 ]. p24 G1 contains a predicted NLS in the aa 122–139 region ( Figure S4a ) that is rich in basic residues ( Figure S3a ), and our results showed that mutant ∆122–139 almost lost its nuclear localization, and failed to bind ds siRNA, block RNA silencing and induce a necrotic response in N. benthamiana ( Figure 4 , Figure 5 , Figure 6 and Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations